E-067 Reducing time to revascularization in acute ischemic stroke. (4th August 2020) - Shownkeen, H; Doerr, A; Togbi-Wonyo, S; Fill, B; Mazumdar, A; Pandya, D; Lindstrom, A; Shownkeen, M
Abstract : Background: Endovascular treatment (EVT) of large vessel occlusions in the treatment of disabling strokes is more effective if reperfusion is achieved quickly. Streamlining protocols from patient presentation to groin puncture can lead to improved timelines to treatment and functional outcomes. Purpose: The purpose of this study was to identify the impact of specific hospital based process improvement strategies in the acute ischemic stroke patient population undergoing endovascular therapy with the specific intent to decrease median arrival to groin puncture. Our multidisciplinary events to review pre and intraprocedure work flow as part of a process improvement (PI) project began in November 2018 during fiscal year (FY) 2019 (9/1/2018–9/1/2019) and implementation of recommendations began FY 2020 (9/1/19- 12/31/19). Methods: The study includes a pre- and post-intervention retrospective review of consecutive patients 18 years or older, hospital admission between September 1, 2016 and December 31, 2019, who underwent EVT for treatment of acute ischemic stroke. Patients experiencing acute stroke within an established hospital admission were excluded from analysis. The primary outcome variables were time from arrival to groin puncture and first pass during the acute ischemic stroke admission. The data points were collected from internal stroke review dataset and anonymized prior to analysis. All but two of our cases used general anesthesia. Results: In FYs 2017 (9/1/16–9/1/17) and 2018 (9/1/17–9/1/18) before intervention our median door to needle times were 94 minutes in FY 2017 (37 patients) and 113 minutes in FY 2018 (48 patients). Our median door to first pass times were 114 minutes in FY 2017 and 139 minutes in FY 2018. Post intervention our door to groin puncture times were 64 minutes in FY 2019 (64 patients) and 56 minutes in FY 2020 (35 patients). Our median door to first pass times were 86 minutes in FY 2019 and 74 minutes in FY 2020. The drop in door to groin puncture and door to first pass times pre and post intervention were statistically significant (P<0.05). Conclusions: Having multidisciplinary team events dedicated to PI alone (which provided education and awareness to multiple stakeholders) resulted in a substantial decrease in median door to groin puncture and door to first pass times. Implementation of hospital based PI initiatives to improve work flow including: early endovascular team activation, a streamlined transport process, a streamlined patient preparation process in the lab, and utilization of a feedback tool resulted in continued improvement in door to groin puncture and first pass times. Disclosures: H. Shownkeen: None. A. Doerr: None. S. Togbi-Wonyo: None. B. Fill: None. A. Mazumdar: None. D. Pandya: None. A. Lindstrom: None. M. Shownkeen: None.